Institutional origins of Islamist political mobilization - Mecham, Quinn (Cambridge University Press, 2017)
"Muslim countries experience wide variation in levels of Islamist political mobilization, including such political activities as protest, voting, and violence. Institutional Origins of Islamist Political Mobilization provides a theory of the institutional origins of Islamist politics, focusing on the development of religious common knowledge, religious entrepreneurship, and coordinating focal points as critical to the success of Islamist activism. Examining Islamist politics in more than 50 countries over four decades, the book illustrates that Islamist political activism varies a great deal, appearing in specific types of institutional contexts. Detailed case studies of Turkey, Algeria, and Senegal demonstrate how diverse contexts yield different types of Islamist politics across the Muslim world"-- Provided by publisher